Short Vilnius Churche’s Inscriptions: Some Problems of Classification and Terminology - Gerliakienė, Veronika (Literatūra, 2015)
Baroque architecture of Lithuanian churches is distinguished by a great amount of various inscriptions. This article deals with short Latin inscriptions, their classification and description. There are eleven types of such texts: explanatory, fundative and donative, occasional, memorial, precautionary, emblematic, votive, like litany, sentential. The last group consists of a few texts, which couldn’t find place among those named above. Inscriptions were written not for (or not only for) decorative purposes. It is possible to speak about joint composition of the text and image (fresco, picture, sculpture, plastic figure), nevertheless the function of the text isn’t aesthetic. Classification given above proves that short inscriptions aimed at teaching, explaining, preventing from misinterpretation, immortalizing an event or a person, and expressing a certain concept corresponding with different forms of art.